2019
DOI: 10.1080/23335432.2019.1671221
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a low-cost webcam recording system for three-dimensional lower limb gait analysis

Abstract: The purposes of this study were to develop and evaluate the test-retest reliability of a specific low-cost three-dimensional webcam recording system (3D-WCRS) and compare its reliability to a standard motion analysis system. Twenty healthy volunteers comprised of 5 males and 15 females with a mean age of 22.90 years and mean BMI of 22.72 kg/m 2 were investigated for angles of hip, knee and ankle joints in three planes while walking at a self-selected speed. Intraclass correlation coefficients (ICCs) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previous studies have developed alternative two-dimensional (2D) methods and compared these with 3D methods for use in clinical settings. [18][19][20][21] 2D measurement using commercial cameras is one method which is relatively inexpensive and easy to apply in field and clinical settings. 22 2D measurements have been used to examine dynamic knee valgus using the frontal plane projection angle (FPPA), which has shown good reliability in performance test such as running, drop jump, and single leg landing, which can provide biomechanical measurements to assess injury risk and progression through treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have developed alternative two-dimensional (2D) methods and compared these with 3D methods for use in clinical settings. [18][19][20][21] 2D measurement using commercial cameras is one method which is relatively inexpensive and easy to apply in field and clinical settings. 22 2D measurements have been used to examine dynamic knee valgus using the frontal plane projection angle (FPPA), which has shown good reliability in performance test such as running, drop jump, and single leg landing, which can provide biomechanical measurements to assess injury risk and progression through treatment.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, due to the increased cost factor and difficulty in accessing the 3D systems, several two-dimensional (2D) methods have been developed and validated. [27][28][29][30] Irawan et al reported that 2D tools for kinematics assessment was a reliable, unexpensive, and easy to use method that can be used in the clinical and research fields to evaluate knee valgus movement based on frontal plane projection angle during drop-jump and single leg landings. 25 The combination of smartphones-Kinovea has been proven to be a valid and reliable instrument for evaluation of joint kinematics and jump performances in different populations.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…In the early days, webcam-based motion captures required markers for the accurate analysis of human body movements. In addition to direct attachment of sphere-shaped objects as markers on the body, certain parts that have significant contrasts to the background may be specified for tracking [12,13]. Because marker-based systems have spatial constraints, a markerless system is essential for use in natural settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its high usability, there is a lack of research on markerless 3D motion capture systems compared to those on other motion capture systems. Many existing studies have separated the upper and lower limbs to analyze their movements, mostly focusing on lower limbs [12,13,[16][17][18]. Because the upper and lower limbs are moved simultaneously in most function activities in daily life, unlike in the laboratory, it is important to measure and analyze them without separation.…”
Section: Introductionmentioning
confidence: 99%